ProcCluster® and procaine hydrochloride inhibit the replication of influenza A virus in vitro - Häring, Clio; Schroeder, Josefine; Jungwirth, Johannes; Löffler, Bettina; Henke, Andreas; Engert, Beatrice; Ehrhardt, Christina (Frontiers in Microbiology, 2024)
Introduction Treatment of influenza A virus infections is currently limited to few direct acting antiviral substances. Repurposing other established pharmaceuticals as antivirals could aid in improving treatment options. Methods This study investigates the antiviral properties of ProcCluster® and procaine hydrochloride, two derivatives of the local anesthetic procaine, in influenza A virus infection of A549, Calu-3 and MDCK cells. Results Both substances inhibit replication in all three of these cell lines in multi-cycle experiments. However, cell line-dependent differences in the effects of the substances on viral RNA replication and subsequent protein synthesis, as well as release of progeny viruses in single-cycle experiments can be observed. Both ProcCluster® and procaine hydrochloride delay endosome fusion of the virus early in the replication cycle, possibly due to the alkaline nature of the active component procaine. In A549 and Calu-3 cells an additional effect of the substances can be observed at late stages in the first replication cycle. Interestingly, this effect is absent in MDCK cells. We demonstrate that ProcCluster® and procaine hydrochloride inhibit phospholipase A2 (PLA2) enzymes from A549 but not MDCK cells and confirm that specific inhibition of calcium independent PLA2 but not cytosolic PLA2 has antiviral effects. Discussion We show that ProcCluster® and procaine hydrochloride inhibit influenza A virus infection at several stages of the replication cycle and have potential as antiviral substances.